Sunny Weather : A 4D BOOK - Lee, Sally , 1943- (Little pebble. All Kinds of Weather, 2019)
"Ah, it is sunny. Put on your sunglasses and find out why we need the sun and sunny days. Bring augmented reality to your students by downloading the free Capstone 4D app and scanning for access to an online article, video, and discussion questions"